2022
DOI: 10.1007/s12028-022-01448-9
|View full text |Cite
|
Sign up to set email alerts
|

Timely and Appropriate Administration of Inhaled Argon Provides Better Outcomes for tMCAO Mice: A Controlled, Randomized, and Double-Blind Animal Study

Abstract: Background: Inhaled argon (iAr) has shown promising therapeutic e cacy for acute ischemic stroke (AIS) and exhibited impressive advantages over other inert gases as a neuroprotective agent. However, the optimal dose, duration and time point of iAr for AIS are unknown. Here, we explored variable iAr schedules and evaluated the neuroprotective effects of acute iAr administration on lesion volume, brain edema, and neurological function in a mouse model of cerebral ischemic/reperfusion (I/R) injury.Methods: Adu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…There were 16 in vitro studies, seven ex vivo studies, and 37 in vivo studies (six of which also included in vitro experiments). 1 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 Details of these studies are presented in the Supplemental materials ( Supplemental Tables S7 and S8 ). The sex of humans, animals, cells, and tissues involved are documented in Supplemental Table S7 (under the column labelled “cell tissue”) and…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 16 in vitro studies, seven ex vivo studies, and 37 in vivo studies (six of which also included in vitro experiments). 1 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 Details of these studies are presented in the Supplemental materials ( Supplemental Tables S7 and S8 ). The sex of humans, animals, cells, and tissues involved are documented in Supplemental Table S7 (under the column labelled “cell tissue”) and…”
Section: Resultsmentioning
confidence: 99%
“…3 , panel a). 18 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 40 , 41 , 43 , 44 , 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 60 , 62 , 63 , 64 , 67 , 68 , 69 , 71 , 73 , 74 , 75 , 76…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Our previous study demonstrated that timely argon administration during ischemia improves neurological outcomes and decreases infarct volumes in the tMCAO mouse model ( He et al., 2022 ), but the underlying mechanism is not clear. In this study, we tested the hypothesis that argon plays a neuroprotective role through mitigating neuroinflammation by regulating microglia/macrophage M1/M2 polarization and inhitibing NLRP3 inflammasome signaling pathway in microglia in the tMCAO mouse model and primary cultured microglia.…”
Section: Introductionmentioning
confidence: 99%